CRYOGENIC RATCHETING OF PRESTRAINED AUSTENITIC STAINLESS STEEL S30408 - LI LeiLei; GAO BingJun; DONG JunHua; CHEN Xu (Jixie qiangdu)
Taking advantage of the EUM-25 K20 tension-torsion fatigue testing machine by CARE,the cryogenic uniaxial ratcheting tests were carried out for the S30408 specimens with and without weld,and with 0%,8%,and 12% pre-strains at110 K. It is shown that ratcheting behavior of specimens with and without weld is closely related to mean stress,amplitude stress and loading history. Because of the softening effect of a small amount of ferrite in weld metal,the initial ratcheting strain of weld specimen and ratcheting strain of weld specimen under small cyclic stress is larger than that of base metal. However,with the increase of plastic deformation,the higher content of alloying elements in weld metal has a more obvious strengthening effect,which makes the subsequent ratcheting strain of weld specimens with a certain number of cycles smaller than that of base metal under larger cyclic stress. The ratcheting strain of specimens with and without weld decreases with the increase of the pre-strain at cryogenic temperature. The accumulation of ratcheting strain can be completely restrained by pre-strain at a small cyclic stress level. S30408 is rate-dependent material at 110 K,and ratcheting strain decreases with the increase of loading rate.